Evaluating Pricing Strategies of Multinational Companies in India’s Manufacturing Industry - Dharan, Ajith (Global journal of Business and Integral Security, 2025)
The Indian market offers enormous opportunities for multinational players - a large population, the growing middle class, increasing income levels and aspirational value for world class brands. The study evaluates the pricing strategies employed by multinational companies (MNCs) in the manufacturing industry in India, utilizing a mixed-method approach to gain comprehensive insights. As India continues to emerge as a significant player in the global manufacturing landscape, understanding the pricing dynamics is crucial for both academic and practical applications. The research combines quantitative analysis of pricing data from various MNCs with qualitative interviews of industry experts and company executives. The quantitative components involve statistical analysis of pricing models, market share, and consumer behavior, allowing for the identification of prevalent pricing strategies such as cost-plus pricing, value-based pricing and competitive pricing. The qualitative component enriches these findings by providing contextual understanding of how cultural, economics, and regulatory factors influence pricing decisions. Preliminary results indicate that MNCs often adapt their global pricing strategies to align with local market conditions while balancing profitability and competitiveness. The study highlights the significance of consumer perceptions and competitive positioning in shaping pricing strategies. Ultimately, this research aims to contribute to the existing literature on pricing strategies in emerging markets and provide actionable insights for multinational companies operating in Indian‘s manufacturing sector.